2019
DOI: 10.1101/695502
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural determinants of protocadherin-15 elasticity and function in inner-ear mechanotransduction

Abstract: 156 Words) 2 , an atypical member of the cadherin superfamily, is essential for vertebrate hearing 3 and its dysfunction has been associated with deafness and progressive blindness. The PCDH15 ectodomain, 4 made of eleven extracellular cadherin (EC1-11) repeats and a membrane adjacent domain (MAD12), assembles 5 as a parallel homodimer that interacts with cadherin-23 (CDH23) to form the tip link, a fine filament necessary 6 for inner-ear mechanotransduction. Here we report X-ray crystal structures of a PCDH15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 141 publications
0
7
0
Order By: Relevance
“…Why? Recent studies using optical tweezers and molecular dynamics simulations suggest that tip link proteins are far more elastic than initially thought 39,40 . Elasticity will allow unbound domains in the B1 state ( Fig.…”
Section: Main Textmentioning
confidence: 96%
See 2 more Smart Citations
“…Why? Recent studies using optical tweezers and molecular dynamics simulations suggest that tip link proteins are far more elastic than initially thought 39,40 . Elasticity will allow unbound domains in the B1 state ( Fig.…”
Section: Main Textmentioning
confidence: 96%
“…6c). As the concentration of Ca 2+ bathing the tip link decreases, the junctions between each EC domain become more flexible due to decreased occupancy of Ca 2+ 8 , and the series elasticity of EC domains is increased 40 . We showed that protein elasticity modifies the extent of avidity under force ( Fig.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, alignments of EC repeat sequences across up to 20 species for intermicrovillar and tip-link cadherins reveal poor conservation for PCDH24 and CDHR5 when compared to CDH23 and PCDH15. Average percent identity is 51.6% for CDH23 EC repeats and 45.5% for PCDH15 repeats, with the N- and C-terminal ends being more conserved than the middle EC repeats (Choudhary et al, 2019; Jaiganesh et al, 2018). In contrast, average percent identity is 16.4% for PCDH24 and 11% for CDHR5, considerably lower when compared to values for CDH23 and PCDH15.…”
Section: Resultsmentioning
confidence: 99%
“…The strength and dynamics of cadherin heterophilic bonds, which are present in systems subjected to mechanical stimuli, might also differ from and provide specific advantages over weak homophilic cadherin complexes that cluster to provide strong adhesiveness. Whether PCDH24 and CDHR5 engage in cis interactions that can lead to more mechanically robust intermicrovillar links, as observed for tip links (Choudhary et al, 2019; Dionne et al, 2018; Ge et al, 2018), or to the formation of larger adhesive complexes in non-microvillar membranes, as observed for classical cadherins and clustered protocadherins (Brasch et al, 2019, 2012; Schreiner and Weiner, 2010), remains to be explored.…”
Section: Discussionmentioning
confidence: 99%